HUBUNGAN AKTIVITAS FISIK, POLA MAKAN, DAN MEROKOK DENGAN KEJADIAN HIPERTENSI PADA LANSIA DI KAMPUNG TUA BAKAU SERIP TAHUN 2022 - Ibrahim; Indria Sari; Muhammad Iqbal Fakhruzzaman (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2023)
Background: Hypertension is a condition in which there is an increase in diastolic pressure that is more than 90 mmHg and systolic above 140 mmHg or while taking hypertension drugs. Methods: This research method used the Correlation Analytic method with a Cross-sectional Study approach. Sampling in this study using total sampling technique. Results: The results of the analysis of the relationship between physical activity, diet, and smoking with the incidence of hypertension in the elderly using the Spearman test obtained a physical activity score (p-value 0.000), eating pattern p-value (0.000), and smoking p-value (0.002). The results of the multivariate test used multiple logistic regression tests (Multiple Regression Logistics) with the results of physical activity with an OR value of 95% CI (4,776).. Conclusion: There is a significant relationship between physical activity, diet, and smoking with the incidence of hypertension in the elderly in Kampung Tua Bakau Serip, and multivariate test results found that physical activity is the most dominant factor in the incidence of hypertension in the elderly in Kampung Tua Bakau Serip 2023 .